Handbook of organizational learning and knowledge management - Easterby-Smith, Mark.; Lyles, Marjorie A. (Chichester, West Sussex : Wiley, 2011)
"The fully revised and updated version of this successful Handbook is welcomed by management scholars world-wide. By bringing together the latest approaches from the leading experts in organizational learning & knowledge management the volume provides a unique and valuable overview of current thinking about how organizations accumulate 'knowledge' and learn from experience. Key areas of update in the new edition are:[bullet] Resource based view of the firm[bullet] Capability management[bullet] Global management[bullet] Organizational culture[bullet] Mergers & acquisitions[bullet] Strategic management[bullet] Leadership"--
pt. 1. Disciplinary perspectives -- pt. 2. Organizational learning and learning organizations -- pt. 3. Knowledge and its management in organizations -- pt. 4. Learning and knowledge in international contexts.
Originally published: Blackwell handbook of organizational learning and knowledge management. 2003.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Organizational learning -- Handbooks, manuals, etc; Knowledge management -- Handbooks, manuals, etc; Apprentissage organisationnel -- Guides, manuels, etc; Gestion des connaissances -- Guides, manuels, etc; BUSINESS & ECONOMICS -- Organizational Behavior; BUSINESS & ECONOMICS -- Mentoring & Coaching; BUSINESS & ECONOMICS -- Training; Knowledge management; Organizational learning; Handbook; handbooks; Handbooks and manuals; Handbooks and manuals; Guides et manuels